Correcting Misperceptions: The Causal Role of Motivation in Corrective Science Communication About Vaccine and Food Safety. Issue 1 (February 2020) - van Stekelenburg, Aart; Schaap, Gabi; Veling, Harm; Buijzen, Moniek
Some people stick to beliefs that do not align with scientific consensus when faced with science communication that contradicts those misperceptions. Two preregistered experiments (total N = 1, 256) investigated the causal role of motivated reasoning in the effectiveness of correcting misperceptions. In both experiments, accuracy-driven reasoning led to a larger corrective effect of a science communication message than reasoning driven by directional motivation. Individuals' default reasoning made them just as receptive to the correction as accuracy-driven reasoning. This finding supports a more optimistic view of human receptivity to science communication than often found in the literature.